The professions, needs-interpretation and legitimacy in the politics of eldercare - Jørgensen, Simon Laumann (Politica, 2019)
Which role should we ascribe citizens and professions in the development of politics of eldercare? The dominant view ascribes them a marginal one. Importantly, this is a classic power struggle within the politics of needs interpretation: Who should be able to determine the legitimate needs in the welfare state? To determine legitimacy in the politics of needs, several researchers point to the relevance of Jürgen Habermas’ complex theory construction. This approach is primarily relevant as it reveals the functions a democratic welfare state should take upon itself to ensure society-wide communication about citizens’ needs. Building on Habermas’ thinking as well as recent developments in care policies, the article argues that we should take sharper notice of how this society-wide communication is challenged by the existence of different experience positions grounded in people’s degree of care dependency. On this basis, it makes sense to ascribe a privileged role to the eldercare professions as bridge builders in the democratic debate concerning legitimacy in the politics of eldercare. This, however, depends on ascribing them a stronger part as needs interpreters in cooperation with care-dependent citizens than recent care policies suggest.